Berberine and inflammatory bowel disease: A concise review. (November 2016) - Habtemariam, Solomon
Graphical abstract: Abstract: Berberine is the principal component of many popular medicinal plants ( e . g . the genus Berberis, Coptis and Hydrastis among others) with a history of thousands of years of usage in traditional medicine. The numerous pharmacological activities of berberine reported in the last two decades have been attracting high level interests both within the scientific community, clinicians and the public at large. Despite enormous amount of efforts have been placed to show its therapeutic value for inflammatory bowel diseases (IBD), however, comprehensive up-to-date review article in this field is not yet available. In this communication, literature data from in vitro and in vivo experiments were scrutinised and concisely presented to demonstrate its anti-IBD potential. Beyond the known general antioxidant and anti-inflammatory effects of berberine, IBD-specific effects including gut epithelial barrier pathology, T cells as emerging targets, antinociceptive and other effects are discussed.